Challenges faced by the tutors of the Polivirtual system - José de Jesús Peinado Camacho (Universidad de Guadalajara, 2021)
The objective of this research was to document experiences on tutorials from the perspective of tutors of the Polivirtual system at the National Polytechnic Institute. The work opted for a qualitative methodology and followed the research question: What challenges do tutors face in the Polivirtual system? The study was non-experimental, with a cross-sectional and exploratory design, and used a nonprobabilistic and heterogeneous sample. The results obtained showed that the tutorial action is based on constant challenges, skills, strategies, digital media and the experiences of the tutors themselves. In addition, the research provided useful information about the tutor and their challenges in the Polivirtual system, while finding new trends and data within this topic, relevant for future and more introspective investigations. It is concluded that the tutorial activity alternates with other academic, administrative, training and even personal activities, which should be understood as challenges faced by tutors, although not generalizable or definitive.